IMPLEMENTATION OF THE INTEN SUWENO INTEGRATED CENTER (STIS) FUNCTION IN INCREASING THE COMPETITIVENESS OF PROSPECTIVE WORKERS WITH DISABILITIES - Barikly, Stanley Baried; Indupurnahayu, Indupurnahayu; Prastowo, Bramastyo Bontas (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This study aims to analyze the implementation of the Integrated Center for Inten Suweno (STIS) in improving the competitiveness of prospective workers with disabilities. Using a qualitative descriptive approach, data were collected through interviews, documentation, and observation. The results of the study show six main findings, namely the limited dissemination of vocational training to remote areas, the incompatibility of the training curriculum with job market trends, obstacles related to the character and background of the beneficiaries, the inconsistent absorption of alumni by partner companies, the existence of stigma from the world of work, and the training period being too short. These findings were analyzed using management theory and human resource management theory and compared with ten previous studies. The study concluded that although STIS plays an important role in empowering persons with disabilities, improvements are needed in curriculum alignment, partnership consistency, and policy support to achieve sustainable competitiveness.